The Website Design and Construction as a Publication Media for MSMEs in the Tembolak Area Using the Laravel Framework - Rubiatun Isnaini; Yuan Sa'adati (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
The development of information technology provides opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their business promotions through digital media. However, MSMEs in the Tembolak area, Jempong Village, Mataram City, do not yet have a centralized information media that can be used to present business information to the public effectively. This condition causes MSME information to remain scattered and difficult to access by potential customers and tourists. This study aims to design and build a website as a publication medium for MSMEs in the Tembolak area using the Laravel framework. The system development method used is the Waterfall method which includes the stages of needs analysis, system design, implementation, and testing. The system design was carried out using UML and ERD, while the system testing used the Black Box Testing method to ensure all functions run according to requirements.